Efektivitas Penerimaan Pajak Sarang Burung Walet dan Kontribusinya Terhadap Pajak Daerah Kabupaten Rokan Hulu - Dwi Fionasari; Adriyanti Agustina Putri; Fachrizon Fachrizon (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2021)
Local own Revenue is an important indicator that is assessed as the level of independence of regional goverments in the financial sector. Efforts to increase PAD can be done by increasing the effectiveness and contribution of local taxes, especially the Swallow’s Nest tax. This study aims to determine the effectiveness and contribution of the walet birdt nest tax to regional original revenue of  Rokan Hulu regency from 2017 to 2019. This study uses a descriptive qualitative approach. The type odata used is quantitative and qualitative data. The data sources are primary data and secondary data. Methods of data collection using the method of documentation and interviews. The data analysis method uses effectiveness analysis and contribution analysis. Based on the analysis, it can be concluded thet the effectiveness of the walet bird’s nest tax on the local revenue of the Upper rokan District from 2017 to 2019 show that it is quite effective. This is because the percentage of effectiveness is less thsn 90%. And the bird’s nest walet tax contribution to the local revenue of the upstream Rokan district from 2017 to 2019  show moderate criteria, this is because the contribution percentage is less than 10%.Keywords: Effectiveness, Contribution, Swallow’s Nest Tax, Local Revanue